Optical shielding for ultracold 39K-Cs binary collisions. Issue 12 (January 2020) - Xie, T; Orbán, A; Dulieu, O; Bouloufa-Maafa, N
Synopsis: The optical shielding efficiency in ultracold collisions is investigated for the first time with atoms of different species ( 39 K-Cs) with a close-coupling approach. The spontaneous emission is taken into account through a complex optical potential. The results show that an efficient shielding can be achieved in the presence of a blue-detuned laser. The role of the light polarization on the shielding efficiency is carefully investigated.